Chloroquine Related to Malaria and its Promising Applications for Covid-19 Treatment - Lopes, Alberto Nicodemus Gomes; Silva, Luciano Barreto (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Objective: this article described the use of chloroquine as an antimalarial agent with potential antiviral indications for COVID-19 infections. Methods: this article consisted of online searches and gray literature whose database included PUBMED Central, BVS/BIREME, Web of Science, Science Direct, Higher Level Personnel Improvement Coordinator (CAPES), Periodic Door (Portal de Periódicos da CAPES, The Cochrane Library, and PROSPERO). Results: chloroquine and hydroxychloroquine have shown appropriate clinical reports when associated with the antibiotic Azithromycin. It has been authorized for the clinical treatment of severe acute forms of COVID infections by countries such as Brazil and the USA. Conclusions: Chloroquine seems to have potential antiviral properties that may be useful in the treatment of these severe acute forms of COVID-19 associated with Azithromycin. Nevertheless, its indication must include ECG monitoring due to the risk of prolongation of QT interval, leading to sudden cardiac death.